Gynecomastia: A systematic review of pharmacological treatments - Berger, Ori; Landau, Zohar; Talisman, Ran (Frontiers in Pediatrics, 2022)
Background: Pubertal gynecomastia (PG), a benign condition with varied reported prevalence, typically appears at 13-14 years-old and is mostly idiopathic and self-limited. Psychologic impairments are common among adolescents with gynecomastia. Surgical intervention is reserved to severe cases and is offered towards the end of puberty. Pharmacological treatment is seldom given by clinicians mainly due to insufficient published data. We conducted this systematic literature review to assess the efficacy, safety, side effects, and complications of pharmacological treatments published. Methods: MEDLINE, Embase, and Cochrane CENTRAL were searched for the terms “gynecomastia", “pubertal”, and “adolescent” in conjunction with medications from the Selective Estrogen Receptor Modulator (SERM), aromatase inhibitors (AI), and androgens groups in different combinations to optimize the search results. Exclusion criteria included: studies based on expert opinion, similar evidence-based medicine levels studies, and studies which discuss gynecomastia in adults. Selected articles were assessed by two authors. Data collected included: the level of evidence, population size, treatment regimen, follow-up, outcomes, complications, and side effects. Results: Of 1425 published studies found and examined meticulously by the authors, only 24 publications met all the study research goals. These were divided into 16 publications of patients treated with SERM, of whom four had AI and four androgens. In general, the data regarding pharmacologic therapy for PG is partial, with insufficient evidence-based research. Tamoxifen and SERM drugs have long been used as treatments for PG. Tamoxifen was the chosen drug of treatment in most of the reviewed studies and found to be effective, safe, and with minimal side effects. Conclusions: Pharmacological treatment as a new standard of care has an advantage in relieving behavioral and psychological distress. Although high quality publications are lacking, pharmacological intervention with tamoxifen is appropriate in select patients. Conduction large-scale high-quality studies are warranted with various drugs.